2013
DOI: 10.5114/pjp.2013.36005
|View full text |Cite
|
Sign up to set email alerts
|

The immunoexpression of glomerular NF-κB in proteinuric patients with proliferative and non-proliferative glomerulopathies

Abstract: Recent studies suggest that NF-κB activation plays an essential role in the activation of mesangial cells and macrophages through the transcriptional induction of inflammatory mediators of glomerular inflammation and injury. The aim of the present study was to determine, using an image analysis system, glomerular immunoexpression of NF-κB (nuclear translocation of p65) in proteinuric patients with proliferative and non-proliferative glomerulopathies. Thirty-six proteinuric patients with idiopathic proliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[24] At the same time, Jilin Chen et al [25] conducted a retrospective cohort study and found that CXCL8 was highly correlated with the prognosis of MN;MMP9, MMP2 and TGFB1 are significantly expressed in patients with MN, which can be used as diagnostic markers of MN. MMP9 is significantly correlated with proteinuria, and MMP9 is significantly increased in patients with proteinuria in nephropathy [26,27] ; Studies have found that glomerular inflammation in MN lesions has different signaling pathways, and PTGS2 and monocytes/ macrophages are involved in the inflammatory process of nephritis [28] ;Tumor necrosis factor (TNF), a pleiotropic cytokine with proinflammatory and immunomodulatory properties, has an important role in renal disease, which predicts renal progression in patients with MN [29] ;Immunohistochemistry confirmed the high expression of VEGFA in MN renal biopsy specimens.…”
Section: Analysis Of Core Target Action Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] At the same time, Jilin Chen et al [25] conducted a retrospective cohort study and found that CXCL8 was highly correlated with the prognosis of MN;MMP9, MMP2 and TGFB1 are significantly expressed in patients with MN, which can be used as diagnostic markers of MN. MMP9 is significantly correlated with proteinuria, and MMP9 is significantly increased in patients with proteinuria in nephropathy [26,27] ; Studies have found that glomerular inflammation in MN lesions has different signaling pathways, and PTGS2 and monocytes/ macrophages are involved in the inflammatory process of nephritis [28] ;Tumor necrosis factor (TNF), a pleiotropic cytokine with proinflammatory and immunomodulatory properties, has an important role in renal disease, which predicts renal progression in patients with MN [29] ;Immunohistochemistry confirmed the high expression of VEGFA in MN renal biopsy specimens.…”
Section: Analysis Of Core Target Action Resultsmentioning
confidence: 99%
“…[ 24 ] At the same time, Jilin Chen et al [ 25 ] conducted a retrospective cohort study and found that CXCL8 was highly correlated with the prognosis of MN;MMP9, MMP2 and TGFB1 are significantly expressed in patients with MN, which can be used as diagnostic markers of MN. MMP9 is significantly correlated with proteinuria, and MMP9 is significantly increased in patients with proteinuria in nephropathy [ 26 , 27 ] ; Studies have found that glomerular inflammation in MN lesions has different signaling pathways, and PTGS2 and monocytes/macrophages are involved in the inflammatory process of nephritis [ 28 ] ;Tumor necrosis factor (TNF), a pleiotropic cytokine with proinflammatory and immunomodulatory properties, has an important role in renal disease, which predicts renal progression in patients with MN [ 29 ] ;Immunohistochemistry confirmed the high expression of VEGFA in MN renal biopsy specimens. VEGFA plays an important role in the pathogenesis of IMN through PI3K/AKT signaling pathway, providing a new target for the treatment of IMN [ 30 ] ;Researchers found that CXCL12 in serum and urine of MN patients was significantly increased, and podocyte proliferation was inhibited in vitro induced podocyte injury model, CXCL12/CXCR4 and phosphorylated STAT3 (p-STAT3) were increased, and CXCL12/CXCR4 and p-STAT3 promoted cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 A similar study reported enhanced glomerular cell NF-kB activation in kidney biopsy specimens from different cohorts of patients with proliferative GN, including membranoproliferative GN, IgA nephropathy, and mesangial proliferative IgM GN. 52 Another group also found enhanced NF-kB activity in podocytes and other glomerular cells in biopsy specimens from patients with lupus nephritis and IgA nephropathy and patients with nonproliferative membranous nephropathy compared with healthy controls. 53 More direct evidence of podocyte activity was indicated in a study that found that podocyte-specific NEMOdeficient mice have faster recovery from anti-GBMe mediated glomerular injury.…”
Section: Discussionmentioning
confidence: 96%